TAR DNA Binding Protein-43 Loss of Function Induced by Phosphorylation at S409/410 Blocks Autophagic Flux and Participates in Secondary Brain Injury After Intracerebral Hemorrhage - Sun, Liang; Zhang, Kai; Zhai, Weiwei; Li, Haiying; Shen, Haitao; Yu, Zhengquan; Chen, Gang (Frontiers in Cellular Neuroscience, 2018)
This study aimed to determine the role of TAR DNA binding protein-43 (TDP-43) in intracerebral hemorrhage (ICH)-induced secondary brain injury (SBI) and its underlying mechanisms. After ICH, expression of TDP-43 in the nucleus was significantly decreased, and its expression in the cytoplasm increased both in vivo and in vitro, which indicates that TDP-43 translocates from the nucleus to the cytoplasm during SBI after ICH. In addition, mutations at S409/410 of TDP-43 could inhibit its phosphorylation, attenuate nuclear loss, and abolish the increase in neuronal apoptosis in the subcortex. Inhibition of TDP-43 phosphorylation attenuated ICH-induced downregulation of mTOR activity and dynactin1 expression, which may relieve blocking of autophagosome-lysosome fusion and the increase of autophagosomal and lysosomal biogenesis induced by ICH. However, knockdown of TDP-43 could worsen ICH-induced SBI. Furthermore, TDP-43 could be dephosphorylated by calcineurin, and calcineurin activity was increased by OxyHb treatment. In conclusion, this study demonstrated that TDP-43 loss-of-function by phosphorylation at S409/410 may block autophagosome-lysosome fusion and induce elevation of LC3II and p62 levels by inhibiting the activity of mTOR and expression of dynactin1. This mechanism may play an important role in ICH-induced SBI, and TDP-43 may be a potential therapeutic target.